Analysis of the Financial Performance of the Ogan Komering Ulu Regency Government for the 2018–2022 Period - Yashinta Shirlei Meilita; Bainil Yuliana; Yuliana Sari (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to evaluate the financial performance of the Regional Government of Ogan Komering Ulu Regency during the 2018–2022 fiscal period and to identify solutions to the challenges faced in financial management to support future improvements. Methodology/Approach: The research employed a documentation study method using official government sources. Primary data were obtained from the regency’s financial statements for 2018–2022, analyzed through financial ratio approaches such as independence, effectiveness, efficiency, and growth ratios. Results/Findings: The analysis revealed that in 2019 and 2022, revenues were insufficient to cover total expenditures. The independence ratio indicated a relatively balanced allocation between operational and capital spending. However, the effectiveness ratio of locally generated revenue (PAD) consistently fell within the ineffective category. The expenditure efficiency ratio was classified as moderately efficient, while PAD growth showed a negative trend across the observed period. Conclusion: The findings emphasize the importance of strategic measures to enhance PAD effectiveness and foster sustainable revenue growth as a foundation for improved fiscal resilience. Limitations: This study is limited to the financial statements and demographic data of Ogan Komering Ulu Regency during 2018–2022, without incorporating broader comparative regional analyses. Contribution: This study contributes by providing empirical evidence on the application of financial ratio analysis in assessing regional government performance. The results offer practical guidance for policymakers in optimizing revenue sources, improving expenditure efficiency, and strengthening fiscal independence. Moreover, the findings provide a comparative reference for other local governments in Indonesia facing similar financial challenges.